Detection of Retinoic Acid in Cosmetics Using Reactive Paper Spray Ionization Mass Spectrometry - Yuzhang Bao; Chenyu Wang; Na Zhang; Jie Li; Song Yuan; Liju Yu; Bin Di; Yang Liu (Molecules)
Chromatography–mass spectrometry typically requires a time-consuming and costly pretreatment to detect illegal additives in cosmetics. Retinoic acid is classified as a prohibited additive in cosmetics by the European Union and China. Therefore, a rapid and convenient method is needed for its detection. In this study, a method for detecting retinoic acid using Reactive Paper Spray Ionization Mass Spectrometry was developed. N′-dimethylpiperazine was used as the derivatization reagent due to its ability to react with carboxyl functional groups at room temperature. Our results indicate that the derivatized retinoic acid compounds obtained using this method exhibited good linearity within the range of 0.0005~0.1 μg·mL−1, achieving a limit of detection of 0.107 ng·mL−1.